The digitalisation in cobalt-chromium framework fabrication. Surface roughness analysis : a pilot study - Aini Hayati Abdul Rahim,; Zubaidah Zanul Abidin,; Norsiah Yunus, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Selective laser melting (SLM) is a new technique in fabricating cobalt-chromium denture framework. However, the surface properties of cobalt-chromium denture framework fabricated using the aforementioned technique have not been widely investigated. The aim of this paper was to investigate the surface roughness of cobalt-chromium alloy in removable partial denture fabricated with SLM technique. Cobalt-chromium denture frameworks were fabricated with two techniques (n = 10); the conventional lost-wax casting (conventional group) and SLM techniques (SLM group). Specimens from the conventional group were subjected to the standard cobalt-chromium denture polishing protocols. No treatment was employed for specimens from the SLM group. All specimens were subjected to surface roughness measurement on polished and fitting surfaces using non-contact optical three-dimensional metrology and surface roughness analysis machine (Infinite Focus Real 3D Alicona). Statistical analysis showed no significant difference in surface roughness between the specimens from conventional and SLM groups (p > 0.05). There was no statistically significant difference in surface roughness between the polished and fitting surfaces of SLM specimens (p > 0.05). Surface roughness quality of the cobalt-chromium denture framework fabricated with the SLM technique is comparable to that fabricated with the conventional lost-wax casting technique. The surface roughness of SLM fabricated cobalt-chromium denture frameworks carries the same surface roughness quality between the polished and fitting surfaces.